A comparative analysis of Japanese and Nigerian operatic theatre (2012)
Several studies in Nigeria and in Japanese theatrical traditions have centred on various elements of either of the two dramatic and theatrical traditions. None so far has comparatively examined the two traditions with the intent of establishing distinct national identities, which are concealed in the theatres of peoples, neither has there been an attempt to comparatively institute universality, conformity or unorthodoxy or lack of it in both theatrical traditions. The interest and explorations, by critics of other far more developed national literatures into Japanese dramatic and theatrical tradition, is an indication that this research effort is pertinent. Most transnational and transcontinental comparative studies on Japanese literary have also not yet ventured beyond the Western world. This pretermits, in the usual manner, the depth and value of African and indeed Nigerian theatrical traditions which are arguably and inextricably rich in comparatives such as trends and forms, elements which have also been globally acclaimed in the international communities. This paper is a comparative examination of Alarinjo and Noh, the operatic theatres of Nigeria and Japan. This analogy is carried out by contrasts; distinguishing the specific features of the forms by comparing differences and is essentially written in counterpoint. This study of the oldest documented professional forms of theatre in Nigeria and Japan seeks to fill some yawing gaps of scholarship in comparative literature, and engage the age long theory of comparative literature as a suitable hypothesis and approach for establishing taxonomies in carrying out this study and other similar studies. It examines how national theatres reflect social, cultural and political issues and also explore the ancient operatic forms to highlight the value of evolving from cultural platforms that are supported by practices that preserve cultural and national identity. This comparatistic inquiry examines movements and trends, motif-types and themes and genre and forms in the operatic theatre of Nigeria and Japan.